Local Halal Cosmetics: How Halal Certification, Brand Image and Influencers Shape Purchase Decisions: Kosmetik Halal Lokal: Bagaimana Sertifikasi Halal, Citra Merek, dan Influencer Membentuk Keputusan Pembelian - Afisa, Ulya Noor; Andni, Riyan (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the factors influencing consumer decisions to purchase Somethinc cosmetics, with a focus on the effects of halal certification, brand image, and influencer endorsements. Utilizing a quantitative approach, data was collected through surveys from 179 consumers who have purchased or used Somethinc products. The sample was selected using purposive sampling, and data analysis included validity, reliability, classical assumption tests, hypothesis testing, and multiple linear regression. The results indicate that Muslim consumers are particularly cautious about choosing cosmetics that align with both their beauty needs and religious values. Influencer recommendations, halal certification, and a positive brand image significantly impact purchasing decisions. These findings provide valuable insights for cosmetic companies like Somethinc, suggesting that improving product quality, building a strong brand, and collaborating with relevant influencers can effectively reach and engage a broader consumer base.